Encyclopedia of everything - Sich, Jenny (DK eyewitness books., 2023)
Become an eyewitness to the world's most incredible nature, science, and historical events, all in one tremendous picture-led reference guide that will take you on a visual tour of everything. Like the hugely successful Eyewitness series itself, Eyewitness Encyclopedia of Everything includes every topic children want to read about. The world's greatest record-breakers, most amazing animals, inspiring history-makers, and cutting-edge technology are all here, in one utterly unputdownable kid's encyclopedia.